Exogenous salicylic acid treatments enhance tolerance to salinity of wheat (Triticum aestivum) plantlets - Purcǎrea, Cornelia; Cachită, Dorina; Petrus, Adriana; Pop, Liviu; Chis, Adriana (Acta Agraria Debreceniensis, 2010)
Salt stress, an abiotic stress, determines modifications of some biochemical indicators, like, antioxidant enzymes, proline (amino acid accumulate in higher plants under salinity stress) content, and some physiological processes including: plant growth and development. In this paper we studied the influence of exogenous treatment of wheat seeds, with 0.1 mM salicylic acid (SA) solution, in the plant response to salt stress. The treatment was applied by presoaking the seeds in the treatment solution for 12 hours before germination. The results showed that exogenous 0.1 mM SA solution, administrated to the wheat cariopses significantly ameliorated the negative effect of salt stress in first week of germination in laboratory conditions.